The Emerging trend Women entrepreneurship in Pakistan - Yaqoob, Samina (Journal of Arts & Social Sciences, 2020)
Though the field of entrepreneurship is continuously growing and mature but still there is a need to explore the role of women entrepreneurship in developing countries. This study highlight, how women execute her entrepreneurial venture while facing different challenges such as cultural, social, and economic constraints etc.?  Moreover, how she can play her best role for the welfare of society in developing countries. Our results showed that female entrepreneurial activities herald the optimization of their social and economic wellbeing, moreover it benefits to society through, wealth creation, poverty reduction etc. In this study Gioia methodology was undertaken to explore the women entrepreneur growth route in Pakistan. By the analysis of women personal experience author identified different social, cultural, financial constraints during the growth phase. The new emerging model provide the useful basis for future research imperatives.